Preoperative visual acuity among cataract surgery patients and countries' state of development: a global study - Shaheen P Shah; Claire E Gilbert; Hessom Razavi; Elizabeth L Turner; Robert J Lindfield (The World Health Organization, 2011)
OBJECTIVE: To describe the preoperative surgical case mix among patients undergoing cataract extraction and explore associations between case mix, country level of development (as measured by the Human Development Index, HDI) and cataract surgery rates (CSRs). METHODS: Ophthalmologists in 50 countries were invited to join the newly-established International Eye Research Network and asked to complete a web-based questionnaire about their eye hospitals. Those who complied received a data collection form for recording demographic and clinical data on 100 consecutive patients about to undergo cataract surgery. Countries were ranked into five HDI categories and multivariable regression was used to explore associations. FINDINGS: Ophthalmologists at 112 eye hospitals (54% of them nongovernmental) in 50 countries provided data on 11 048 cataract procedures over 9 months in 2008. Patients whose visual acuity (VA) before surgery was < 6/60 in the better eye comprised 47% of the total case mix in poorly developed countries and 1% in developed countries (P < 0.001). Overall, 72% of the eyes undergoing surgery had a VA < 6/60. Very low VA before cataract surgery was strongly associated with poor development at the country level and inversely associated with national CSR. CONCLUSION: The proportion of patients with very poor preoperative VA is a simple indicator that can be easily measured periodically to monitor progress in ophthalmological services. Additionally, the internet can be an effective tool for developing and supporting an ophthalmological research network capable of providing a global snapshot of service activity, particularly in developing countries.